Forensic Linguistic Analysis of Wills Written by Deceased Lovers in Tana Toraja - Prosawita Ririh Kusumasari (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study aims to describe the content and linguistic elements of wills content by lovers who were found dead in Tana Toraja and analyze the factors that cause suicide. This research uses descriptive qualitative text analysis methods. The source of data was obtained from the wills of lovers who were found dead in Tana Toraja in the form of written data, excerpts, or entire documents containing a description of the letter. Data analysis is a reading technique, understanding of suicide cases, and linguistic analysis. The stages of data analysis are as follows: case studies deepening understanding, reading/studying data, marking keywords and ideas contained in the data, studying those keywords, trying to find themes derived from data, and writing down 'models' found based on coding that has been done.  The content of the linguistic forensic text of suicide cases uses vocabulary that is unusual in the context, direct speech that refers to remorse, inferiority, warning, mentioning something necessary, desirable things, no hesitation in action, and Factors that cause suicide cases.